The Effectiveness of Used Knee Decker to Knee Pain Complaints in Running Trail’s Runner - Fathi, Muhammad; Syaifuddin, Muhammad; Hakim, Muhammad Nur Rohman (Poltekkes Kemenkes Jakarta I, 2025)
Background: Running performance is influenced by environmental and geographical factors, particularly terrain variations like slopes in trail running. Such conditions increase injury risk, especially to the lower extremities, with the knee joint being highly vulnerable. Knee deckers—elastic supports available in multiple sizes—are designed to mitigate injury risks by enhancing joint flexibility, providing stabilization, and reducing pain during daily activities or sports. Aim: To evaluate the effectiveness of knee deckers in alleviating knee pain among trail runners. Methods: A quasi-experimental study with a one-group pretest-posttest design was conducted. From a population of 163 trail runners, 30 participants were selected via purposive sampling based on inclusion/exclusion criteria. Pain levels were assessed before and after knee decker use. Results: Wilcoxon test analysis revealed a statistically significant reduction in knee pain (p = 0.000, p < 0.05), confirming the intervention’s effectiveness. Conclusion: Knee deckers significantly reduce knee pain in trail runners, supporting their utility for injury prevention and pain management.